Fruit color, physiological disorders and diseases of 'Gala' and 'Fuji' apples sprayed with aminoethoxyvinylglycine Coloração do fruto, distúrbios fisiológicos e doenças em maçãs 'Gala' e 'Fuji' pulverizadas com aminoetoxivinilglicina - do Amarante C.V.T.* (2010)
The objective of this work was to study the effects of preharvest spraying of 'Gala' and 'Fuji' apple trees with aminoethoxyvinylglycine (AVG) in fruit quality and incidence of physiological disorders and diseases. The experiments were carried out in 2005 and 2006, with AVG sprayed (30 days before anticipated fruit harvest) at the doses of 0, 125 and 250 mg L-1, and also at the dose of 62.5 mg L-1 in 2006. In 'Gala' apples, the increase of AVG dose delayed red color development and reduced the water loss permanence of the skin. For this cultivar, the preharvest treatment with AVG increased the incidence of bitter pit, and reduced the incidence of scald, stem-end splitting and decay on fruits assessed after cold storage (three months at 0±0.5°C/90-95% RH), followed by one week of shelf life (20±4°C/60-70% RH). The increase in AVG dose reduced the incidence and severity of watercore in late harvested 'Fuji' apples. The product increased the severity of 'Gala' leaf spot (Glomerella cingulata).